2002
DOI: 10.5703/1288284313251
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Curing Conditions on Strength Properties and Maturity Development of Concrete

Abstract: IntroductionThe main objectives of this project were to establish a correlation between maturity development and degree of hydration of cement and to establish equivalent curing methods for concrete specimens that can accurately represent the curing conditions of concrete in pavement. To achieve these objectives, the following tasks were performed.1. The maturity development of cement in relation to cement hydration was evaluated. 2. The influences of different specimen curing conditions and specimen types on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…[4] report says a maximum of 15% lower modulus of elasticity of recycled aggregate concrete made with coarse recycled aggregate and natural sand.Seyed-Hassan Bagheri-Zadeh1; Hyoungkwan Kim2; Scott Hounsell3; Charles R. Wood4; Hamid Soleymani5; and Michael King6 (2007) [5] in their paper titled "Field Study of Concrete Maturity Methodology in Cold Weather", they reached to conclusions that, the concrete maturity method has been available for more than50 years, but its actual application in the construction industry has been quite slow.Al-Feel J R1 and Al-Saffar N S2 (2008) [6] in their paper titled "Properties of Self Compacting Concrete at Different Curing Condition and their Comparison with properties of Normal Concrete", concluded that;1) The compressive and tensile strength of Selfcompacting concrete were higher than those of ordinary concrete at all considered ages and for all curing condition The SCC gave high early strength (before 28-days).S. Newbolds1, J. Olek2, (2001) [7] in their research titled "The Influence of Curing Conditions on Strength Properties and Maturity Development of Concrete", concluded that, based on the research results presented in this document. Ronald G. Burg,(1996) [8] in his paper titled "The Influence of Casting and Curing Temperature on the Properties of Fresh and Hardened Concrete", Concluded that based on the results of this laboratory program, 1) As concrete mix temperature is increased from23°C (73"F), slump will decrease approximately 20mm for each 10°C increase in temperature (0.8 in.…”
Section: Literature Reviewmentioning
confidence: 98%
“…[4] report says a maximum of 15% lower modulus of elasticity of recycled aggregate concrete made with coarse recycled aggregate and natural sand.Seyed-Hassan Bagheri-Zadeh1; Hyoungkwan Kim2; Scott Hounsell3; Charles R. Wood4; Hamid Soleymani5; and Michael King6 (2007) [5] in their paper titled "Field Study of Concrete Maturity Methodology in Cold Weather", they reached to conclusions that, the concrete maturity method has been available for more than50 years, but its actual application in the construction industry has been quite slow.Al-Feel J R1 and Al-Saffar N S2 (2008) [6] in their paper titled "Properties of Self Compacting Concrete at Different Curing Condition and their Comparison with properties of Normal Concrete", concluded that;1) The compressive and tensile strength of Selfcompacting concrete were higher than those of ordinary concrete at all considered ages and for all curing condition The SCC gave high early strength (before 28-days).S. Newbolds1, J. Olek2, (2001) [7] in their research titled "The Influence of Curing Conditions on Strength Properties and Maturity Development of Concrete", concluded that, based on the research results presented in this document. Ronald G. Burg,(1996) [8] in his paper titled "The Influence of Casting and Curing Temperature on the Properties of Fresh and Hardened Concrete", Concluded that based on the results of this laboratory program, 1) As concrete mix temperature is increased from23°C (73"F), slump will decrease approximately 20mm for each 10°C increase in temperature (0.8 in.…”
Section: Literature Reviewmentioning
confidence: 98%